High-temperature CO2 trapping material resistant to sulfur oxides, nitrogen oxides and oxygen
By optimizing the molar ratio of silicon source and impurity components, high-temperature CO2 capture materials that resist sulfur oxides, nitrogen oxides and oxygen are prepared, which solves the sintering and stability of Li4SiO4 in high-temperature CO2 capture materials, and achieves efficient CO2 capture in complex flue gas environments.
Patent Information
- Application Number
- CN202510490107.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-07-25
AI Technical Summary
The existing Li4SiO4 high-temperature CO2 capture materials have sintering problems during the CO2 adsorption and desorption cycle, which has poor circulation stability and is sensitive to CO2 partial pressure, which cannot effectively resist the influence of SO2, NOx and O2 in flue gas, limiting its application in industrial flue gas environment.
High-temperature CO2 capture materials are prepared by solid phase method by using silicon-containing precursors containing high Taman temperature impurity components (such as Fe, Al, Mg, etc.) and lithium-containing compounds containing high Taman temperature impurity components (such as Na, K, etc.), and lithium-containing compounds, to optimize the molar ratio of silicon source to impurity components, and form the main adsorption material Li4SiO4 and adsorption material, to enhance the anti-sulfur oxide, nitrogen oxide and oxygen properties of the material.
Under low CO2 concentration conditions, the material exhibits excellent adsorption performance and cycling stability, and can maintain stable adsorption capacity under flue gas conditions, significantly improving the capture efficiency and durability in low-concentration CO2 environments and in complex flue gases.
Smart Images

Figure CN120361854A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-temperature CO2 capture material resistant to sulfur oxides, nitrogen oxides, and oxygen, and a preparation method thereof. Background Art
[0002] CO2 is one of the main greenhouse gases causing global warming. Since 1880, the global temperature has risen by at least 1.1 °C. The increase in the concentration of CO2 in the atmosphere is mainly attributed to the combustion of fossil fuels in industry. Therefore, capturing CO2 from flue gas is a key strategy to mitigate greenhouse gas emissions.
[0003] Using solid adsorbents for CO2 capture is a very promising technology, and its advantages are mainly reflected in a wide adsorption temperature range, low waste emissions during the regeneration process, and environmentally friendly waste adsorbent treatment methods.
[0004] Among high-temperature CO2 solid adsorbents, Li4SiO4 is considered to be one of the most promising materials due to its high CO2 capture capacity and low regeneration temperature. However, during the CO2 adsorption and desorption cycles, Li4SiO4 still faces obvious sintering, which affects its cycle stability. In addition, the CO2 adsorption capacity of Li4SiO4 shows a high dependence on the CO2 partial pressure. Under low CO2 partial pressure conditions, its adsorption capacity decreases significantly. The research by Zhang et al. shows that Li4SiO4 synthesized using silicon-containing precursors such as TS-1, ZSM-5, and MCM-48 exhibits poor cycle stability. In addition, Li4SiO4 synthesized using commercial SiO2 and MCM-41 is highly sensitive to the CO2 concentration, and its adsorption capacity under 20% CO2 conditions is only 50% of that in a pure CO2 environment. In addition, in the actual industrial flue gas environment, the performance of the adsorbent in the CO2 capture system is often restricted by the combined action mechanism of multi-component polluted gases. In addition to CO2, components such as SO2, NO x and O2 in flue gas can significantly affect the adsorption capacity and cycle stability of the adsorbent through multiple pathways. Therefore, synthesizing a high-temperature CO2 capture material with strong adsorption performance, high cycle stability, sulfur resistance, nitrogen oxide resistance, and strong antioxidant performance is crucial for the large-scale application of carbon capture technology. Summary of the Invention
[0005] The purpose of the present invention is to provide a high-temperature CO2 capture material resistant to sulfur oxides, nitrogen oxides, and oxygen, and a preparation method thereof.
[0006] To solve the above technical problems, the technical solution of the present invention is as follows:
[0007] A high-temperature CO2 capture material resistant to sulfur oxides, nitrogen oxides, and oxygen, which is prepared by using a silicon source such as a silicon-containing precursor, natural silicon-containing ore, or other silicon-containing waste containing a Gaudin temperature impurity component (such as Fe, Al, Mg, etc.) and an auxiliary adsorption impurity component (such as Na, K, etc.), and reacting with a lithium-containing compound through a solid-phase method; it includes a main adsorption material Li4SiO4 and an auxiliary adsorption material.
[0008] For the high-temperature CO2 capture material described above, the auxiliary adsorption material is the Gaudin temperature impurity component and alkali metal or alkaline earth metal impurity component present in the silicon source.
[0009] For the high-temperature CO2 capture material described above, the adsorption material prepared with the molar ratio of silicon to the Gaudin temperature impurity component (Si / X) in the silicon source within the range of 3.76 - 5.68 has the best effect, where X is the Gaudin temperature impurity element.
[0010] For the high-temperature CO2 capture material described above, the adsorption material prepared under the condition that the molar ratio of silicon to the auxiliary adsorption impurity component (Si / Y) in the silicon source is 20.6 or lower has the best effect, where Y is the alkali metal or alkaline earth metal impurity element.
[0011] For the high-temperature CO2 capture material described above, the lithium-silicon molar ratio (Li / Si) is 3:1 - 10:1, preferably 4:1.
[0012] For the high-temperature CO2 capture material described above, the CO2 adsorption temperature is 400 - 700 °C, preferably 500 - 650 °C, more preferably 600 °C.
[0013] The preparation method of the silicon-containing precursor used for the high-temperature CO2 capture material described above includes the following steps: (1) Add a structure-directing agent, a pH regulator, and deionized water to a beaker and mix at room temperature; (2) Then add the silicon source to the mixed solution and continue stirring; (3) Continue to add inorganic salts of metal elements with Gaudin temperature characteristics (such as FeCl3, Fe(NO3)3, Fe2(SO4)3, AlCl3, Al2(SO4)3, Al(NO3)3, Mg(NO3)3, etc.) and alkali metal or alkaline earth metal impurity components (such as Na2CO3, K2CO3, etc.) to the mixed solution in proportion, and form a gel-like mixture through mixing and stirring; (4) Subsequently, perform a hydrothermal reaction on the obtained gel-like mixture; (5) Finally, filter and wash with deionized water until the sample is neutral, and calcine after drying to obtain the silicon-containing precursor containing a Gaudin temperature impurity component (such as Fe, Al, Mg, etc.) and an auxiliary adsorption impurity component (such as Na, K, etc.).
[0014] In the described preparation method, the structure-directing agent in step (1) is tetramethylammonium, tetraethylammonium, tetrapropylammonium, cetyltrimethylammonium bromide, block copolymer, fluoride, etc.
[0015] In the described preparation method, the lithium-containing compound in step (1) is lithium nitrate, lithium carbonate, lithium hydroxide, lithium oxide, etc.
[0016] In the described preparation method, the pH regulator in step (1) is ammonia water, NaOH, KOH, organic base (such as TMAOH, TEAOH), hydrochloric acid, sulfuric acid, acetic acid, ammonia-ammonium chloride buffer solution, phosphate buffer solution, etc.
[0017] In the described preparation method, the silicon source added to the mixed solution in step (2) is sodium silicate, silica sol, silica gel, tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate (TMOS), etc.
[0018] In the described preparation method, the hydrothermal temperature in step (4) is 80 - 130 °C, and the hydrothermal time is 12 - 24 hours.
[0019] In the described preparation method, the calcination temperature in step (5) is 450 - 600 °C, and the calcination time is 4 - 6 hours.
[0020] The preparation method of the high-temperature CO₂ capture material includes the following steps: (1) Mechanically mix the above-mentioned silicon-containing precursor or qualified natural silicon-containing ore and silicon-containing waste as the silicon source with the lithium-containing compound and the grinding aid; the silicon source needs to contain specific proportions of high-temperature impurity components (such as Fe, Al, Mg, etc.) and adsorption-promoting impurity components (such as Na, K, etc.); (2) After drying the mixture, calcine it at a high temperature to obtain the high-temperature CO₂ capture material.
[0021] In the described preparation method, the mass percentage of SiO₂ in the natural silicon-containing ore and silicon-containing waste in step (1) is between 32 - 90 wt%, such as perlite, diatomite, wollastonite, blast furnace slag, vermiculite or fly ash, etc.
[0022] In the described preparation method, the lithium-containing compound in step (1) is lithium nitrate, lithium carbonate, lithium hydroxide, lithium oxide, etc.
[0023] The grinding aid is deionized water, ethanol, methanol, acetone, etc.
[0024] In the described preparation method, the calcination temperature in step (2) is 600 - 800 °C, preferably 750 °C.
[0025] The high-temperature CO2 capture material provided by the present invention can have adsorption performance in a relatively wide high-temperature range of 400-700 °C. Compared with pure Li4SiO4 prepared from commercial SiO2, the material prepared using a silicon source that meets specific requirements (the molar ratio of silicon to high-Tammann temperature impurity components in the silicon source is in the range of 3.76-5.68, and the molar ratio of silicon to co-adsorbing impurity components in the silicon source is 20.6 or lower) exhibits excellent adsorption performance under low-concentration CO2 conditions and demonstrates excellent stability during cyclic use, proving its reliability and durability in long-term use. In addition, the adsorption performance of this material can still maintain a stable adsorption capacity under flue gas conditions. The above characteristics give this material significant technical advantages and application potential in the cyclic application scenarios of low-concentration CO2 capture and flue gas conditions. Description of the Drawings
[0026] Figure 1 Performance graph of the saturated CO2 adsorption capacity of the characteristic silicon source-Li4SiO4 high-temperature CO2 capture material prepared by the present invention varying with the adsorption temperature under low CO2 concentration.
[0027] Figure 2 Low-concentration CO2 adsorption performance graph of the nY-Li4SiO4 high-temperature CO2 capture material prepared by the present invention with different addition amounts of co-adsorbing impurity components.
[0028] Figure 3 Adsorption-desorption cycle performance graph of the nX-Li4SiO4 high-temperature CO2 capture material prepared by the present invention with different addition amounts of high-Tammann temperature impurity components.
[0029] Figure 4 Adsorption-desorption cycle performance graph of the characteristic silicon source-Li4SiO4 high-temperature CO2 capture material prepared by the present invention under flue gas conditions.
[0030] Figure 5 Comparison graph of the saturated CO2 adsorption capacity of the characteristic silicon source-Li4SiO4 high-temperature CO2 capture material prepared by the present invention and the comparative sample SiO2-Li4SiO4 high-temperature CO2 capture material under low-concentration CO2 conditions.
[0031] Figure 6 Comparison graph of the adsorption-desorption cycle performance of the characteristic silicon source-Li4SiO4 high-temperature CO2 capture material prepared by the present invention and the comparative sample SiO2-Li4SiO4 high-temperature CO2 capture material. Detailed Description of the Invention
[0032] The present invention provides a high-temperature CO2 capture material resistant to sulfur oxides, nitrogen oxides and oxygen, and a preparation method thereof. The CO2 capture material has excellent CO2 adsorption capacity and cycle stability under low CO2 concentration conditions. In the present invention, a series of high-temperature CO2 capture materials are prepared by a solid-phase method by changing the type of silicon source and lithium-containing compounds, and their adsorption performance and cycle stability under low CO2 concentration are tested. The specific implementation method takes the preparation method of perlite-Li4SiO4 as an example. It is found during the experiment that the naturally occurring high-temperature impurity components and co-adsorbing impurity components in the silicon source have a great influence on the CO2 adsorption performance and adsorption-desorption cycle stability of the adsorbent. Therefore, the optimal proportion of various impurity components in the silicon source used for the adsorbent is explored, and a series of silicon sources meeting the requirements are prepared according to the exploration results to prepare adsorbents with strong adsorption performance and high adsorption-desorption cycle stability. The present invention will not be limited to these embodiments shown herein, but can be applied to a wider range consistent with the principles and novel features disclosed herein.
[0033] Example 1. CO2 capture materials prepared from different types of silicon-containing ores
[0034] (1) Preparation method of perlite-Li4SiO4 adsorbent (solid-phase method)
[0035] Put 0.8335 g of perlite and 2.99 g of LiNO3 into an agate mortar, ensure that the Li / Si molar ratio in the mixture is 4, use ethanol as the grinding medium, and grind thoroughly to ensure uniform mixing of the materials. Dry the obtained mixture at 60 °C for 12 hours. Then put the dried powder into an alumina ceramic crucible and calcine it at 750 °C for 6 hours. Finally, grind the calcined material into fine and uniform powder to obtain the final perlite-Li4SiO4 adsorbent.
[0036] The preparation method of diatomite-Li4SiO4 adsorbent is different from that of perlite-Li4SiO4 adsorbent in Example 1 in that 0.727 g of diatomite and 2.99 g of LiNO3 are put into an agate mortar to ensure that the Li / Si molar ratio in the mixture is 4.
[0037] The preparation method of wollastonite-Li4SiO4 adsorbent is different from that of perlite-Li4SiO4 adsorbent in Example 1 in that 1.155 g of wollastonite and 2.99 g of LiNO3 are put into an agate mortar to ensure that the Li / Si molar ratio in the mixture is 4.
[0038] The preparation method of the S95-Li4SiO4 adsorbent is different from that of the perlite-Li4SiO4 adsorbent in Example 1 in that 1.947 g of S95 blast furnace slag and 2.99 g of LiNO3 are placed in an agate mortar to ensure that the Li / Si molar ratio in the mixture is 4.
[0039] The preparation method of the vermiculite-Li4SiO4 adsorbent is different from that of the perlite-Li4SiO4 adsorbent in Example 1 in that 1.583 g of vermiculite and 2.99 g of LiNO3 are placed in an agate mortar to ensure that the Li / Si molar ratio in the mixture is 4.
[0040] The preparation method of the fly ash-Li4SiO4 adsorbent is different from that of the perlite-Li4SiO4 adsorbent in Example 1 in that 1.192 g of fly ash and 2.99 g of LiNO3 are placed in an agate mortar to ensure that the Li / Si molar ratio in the mixture is 4.
[0041] (2) CO2 adsorption capacity test method of the adsorbent
[0042] The CO2 adsorption performance test experiment was carried out in a Q50TA Instruments thermogravimetric analyzer (TGA). The sample amount was about 10 mg, and it was adsorbed for 120 min under the conditions of 600 °C and 20% CO2. The CO2 adsorption amount of the material was obtained by converting the mass difference of the sample before and after adsorption. The CO2 adsorption capacity of the CO2 capture materials prepared from different types of silicon-containing ores was determined by the above CO2 adsorption performance test method. The test results (as shown in Table 1) show that the adsorption effects of the CO2 capture materials prepared from different types of silicon-containing ores are different at low CO2 concentrations. Among them, the perlite-Li4SiO4 adsorbent has the highest adsorption capacity, reaching 25.1 wt%.
[0043] Table 1 Influence test of using different types of silicon-containing ores on the prepared CO2 capture materials (adsorption temperature is 600 °C, CO2 concentration is 20%)
[0044] Silicon-containing ore types Perlite Diatomite Wollastonite S95 slag Vermiculite Fly ash Adsorption capacity (wt%) 25.1 18.5 15 13.6 12.9 6.3
[0045] Example 2. Influence of adsorption temperature on the adsorption performance of CO2 capture materials prepared from silicon-containing ores
[0046] To systematically explore the influence of adsorption temperature on the adsorption performance of the adsorbent, the perlite-Li4SiO4 adsorbent was selected as the research object, and its CO2 adsorption performance was tested under different adsorption temperatures (500 - 650 °C). The results are shown in Table 2 and Figure 1As shown, through comparison, it can be seen that the perlite-Li4SiO4 adsorbent has the fastest CO2 adsorption rate at 600 °C and a relatively high adsorption capacity. After 2 hours of adsorption in a 20% CO2 atmosphere, the adsorption amount reaches 25.1 wt%.
[0047] Table 2 Effect of adsorption temperature on the adsorption performance of perlite-Li4SiO4 adsorbent (CO2 concentration is 20%, adsorption time is 2 hours)
[0048] Adsorption temperature (°C) 500 550 600 650 Adsorption capacity (wt%) 23.3 26.1 25.1 7.3
[0049] Example 3. Influence of co-adsorbing impurity components in silicon-containing ores on Li4SiO4 adsorbent
[0050] (1) Preparation method of Na-Li4SiO4 adsorbent (solid-phase method)
[0051] Place 0.65 g of SiO2 and 2.99 g of LiNO3 in an agate mortar, ensure that the Li / Si molar ratio in the mixture is 4, and add 0.05556 g of Na2CO3 to the mixture. Use ethanol as the grinding medium and mix the mixture thoroughly in the agate mortar. Dry the obtained mixture at 60 °C for 12 hours. Then transfer the obtained mixture to an alumina ceramic crucible and heat it at 750 °C for 6 hours. After cooling, grind it into powder with an agate mortar to obtain the final Na-Li4SiO4.
[0052] The preparation method of 0.25Na-Li4SiO4 adsorbent is different from that of Na-Li4SiO4 adsorbent in Example 3 in that 0.01389 g of Na2CO3 is added to the mixture.
[0053] The preparation method of 0.5Na-Li4SiO4 adsorbent is different from that of Na-Li4SiO4 adsorbent in Example 3 in that 0.02778 g of Na2CO3 is added to the mixture.
[0054] The preparation method of 1.5Na-Li4SiO4 adsorbent is different from that of Na-Li4SiO4 adsorbent in Example 3 in that 0.08334 g of Na2CO3 is added to the mixture.
[0055] The preparation method of 2Na-Li4SiO4 adsorbent is different from that of Na-Li4SiO4 adsorbent in Example 3 in that 0.11112 g of Na2CO3 is added to the mixture.
[0056] The preparation method of the SiO2-Li4SiO4 adsorbent is different from that of the Na-Li4SiO4 adsorbent in Example 3 in that Na2CO3 is not added to the mixture.
[0057] (2) CO2 adsorption capacity test of the adsorbent The adsorption performance of nNa-Li4SiO4 adsorbents with different silicon-sodium molar ratios (5.1 - 41.2) was determined using the CO2 adsorption capacity test method in Example 1. The adsorption capacity test results ( Figure 2 and Table 3) show that the adsorption amount of 0.25Na-Li4SiO4 is 20.4 wt%. When the Na doping amount is increased to 0.5Na-Li4SiO4, the adsorption amount significantly increases to 28.1 wt%. Further increasing the Na doping amount can improve the adsorption kinetics of Li4SiO4, but has no significant effect on the overall adsorption capacity. These findings indicate that even a very small amount of Na doping can significantly improve the adsorption ability of Li4SiO4 at low CO2 concentrations. However, sodium doping beyond a certain threshold is mainly beneficial for adsorption kinetics rather than capacity. Therefore, at low CO2 concentrations, the optimal Na content of this adsorbent corresponds to a silicon-sodium molar ratio less than or equal to 20.6.
[0058] Table 3 CO2 adsorption amounts of adsorption materials with different sodium contents (CO2 concentration is 20%, adsorption time is 2 hours)
[0059] Si / Na molar ratio 5.1 6.9 10.3 20.6 41.2 1:0 Adsorption capacity (wt%) 28.8 27.3 28 28 20.4 16.8
[0060] Example 4. Influence of high-temperature impurity components in silicon-containing ores on the Li4SiO4 adsorbent
[0061] (1) Preparation method of the Al-Li4SiO4 adsorbent (solid-phase method)
[0062] 0.65 g of SiO2 and 2.99 g of LiNO3 were placed in an agate mortar to ensure that the Li / Si molar ratio in the mixture was 4, and 0.0975 g of Al2O3 was added to the mixture. Ethanol was used as the grinding medium, and the mixture was thoroughly mixed in the agate mortar. The obtained mixture was dried at 60 °C for 12 hours. Then the obtained mixture was transferred to an alumina ceramic crucible and heated at 750 °C for 6 hours. After cooling, it was ground into powder with an agate mortar to obtain the final Al-Li4SiO4.
[0063] The preparation method of the 0.5Al-Li4SiO4 adsorbent is different from that of the Al-Li4SiO4 adsorbent in Example 4 in that 0.04875 g of Al2O3 is added to the mixture.
[0064] The preparation method of the 1.5Al-Li4SiO4 adsorbent is different from that of the Al-Li4SiO4 adsorbent in Example 4 in that 0.14625 g of Al2O3 is added to the mixture.
[0065] The preparation method of the 2Al-Li4SiO4 adsorbent is different from that of the Al-Li4SiO4 adsorbent in Example 4 in that 0.195 g of Al2O3 is added to the mixture.
[0066] The preparation method of the SiO2-Li4SiO4 adsorbent is different from that of the Al-Li4SiO4 adsorbent in Example 4 in that no Al2O3 is added to the mixture.
[0067] (2) CO2 adsorption-desorption cycle performance test of the adsorbent
[0068] Use a Q50TA Instruments thermogravimetric analyzer (TGA) to test the CO2 adsorption-desorption cycle performance of different samples. Weigh about 10 mg of the sample and adsorb it for 20 min at 600 °C under 100% CO2 / N2 conditions. Then, keep the temperature unchanged and desorb it for 20 min in a high-purity N2 atmosphere. This is one cycle, and so on.
[0069] Use the above adsorption-desorption cycle performance test method to determine the cycle use performance of nAl-Li4SiO4 adsorbents with different silicon-aluminum molar ratios (2.8 - 11.3). The detection results of the adsorption-desorption cycle performance ( Figure 3 and Table 4) show that during the entire adsorption-desorption cycle, the adsorption capacity of SiO2-Li4SiO4 decreased by 12 wt%. The addition of Al effectively improved the cycle stability of the Li4SiO4 material. For 0.5Al-Li4SiO4, it showed a similar activation process to SiO2-Li4SiO4, and the maximum adsorption capacity after 7 cycles was 20.7 wt%. After 100 cycles, the adsorption loss decreased to 9.8 wt%, but the cycle stability was still relatively poor. As the Al doping amount increased, the cycle stability improved. For the Al-Li4SiO4 with a higher doping level, the material showed relatively stable performance during the adsorption-desorption cycle. The adsorption amount reached 19.4 wt% at the 15th cycle and decreased to 15.1 wt% at the 100th cycle, with an overall loss of 4.3 wt%. 1.5Al-Li4SiO4 had the smallest adsorption loss (2.8 wt%) during the cycle, but its maximum adsorption capacity was only 12.5 wt%. The cycle stability of 2Al-Li4SiO4 was similar to that of 1.5Al-Li4SiO4. Considering the adsorption activity and cycle stability comprehensively, the optimal Al content of this adsorbent corresponded to a silicon-aluminum molar ratio of 3.8 - 5.6.
[0070] Table 4 Influence of Different Aluminum Contents on the CO2 Adsorption-Desorption Recycling Performance of Adsorbents
[0071] Si / Al molar ratio 2.8 3.8 5.6 11.3 1:0 Adsorption capacity after activation (wt%) 12.7 12.5 19.4 20.7 19.9 Adsorption capacity in the 100th cycle (wt%) 9.7 9.7 15.1 10.9 7.8 Total adsorption loss in the cycle (wt%) 3 2.8 4.3 9.8 12.1
[0072] Example 5. Directional Regulation of Impurity Components in the Adsorbent
[0073] (1) Directional Preparation of Silicon Source M' Containing Impurity Components
[0074] Mix 33.5 g of CTAB, 13 mL of ammonia water, and 167 mL of deionized water at room temperature for 30 minutes, then add 14.4 mL of TEOS to the mixed solution and continue stirring for 1 hour. After that, add 4.298 g of Al(NO3)3·9H2O, 0.333 g of anhydrous Na2CO3, 0.257 g of anhydrous K2CO3, 0.328 g of Fe(NO3)3·9H2O, 0.089 g of CaCl2, 0.064 g of Mg(NO3)2·6H2O, and 0.02 g of TiO2 to the solution according to the elemental ratio in perlite ore. After 2 hours of mixing and stirring, a gel-like mixture is formed. Subsequently, perform hydrothermal reaction on the obtained gel-like mixture. The reaction conditions are: hydrothermal at 100 °C for 24 hours. Finally, filter and wash with deionized water until the sample is neutral, and calcine at 550 °C for 6 hours to remove the template agent, obtaining the final silicon source M'.
[0075] The preparation method of 1.25Al-M' silicon source is different from that of silicon source M' in Example 5 in that the addition amount of Al(NO3)3·9H2O is increased to 5.3725 g.
[0076] The preparation method of 1.5Al-M' silicon source is different from that of silicon source M' in Example 5 in that the addition amount of Al(NO3)3·9H2O is increased to 6.447 g.
[0077] (2) Directional Preparation of Adsorbent M'-L Containing Impurity Components
[0078] Place 0.83 g of silicon source M' and 2.99 g of LiNO3 in an agate mortar, ensure that the Li / Si molar ratio in the mixture is 4, use ethanol as the grinding medium, and mix the mixture thoroughly in the agate mortar. Dry the obtained mixture at 60 °C for 12 hours. Then transfer the obtained mixture to an alumina ceramic crucible and heat it at 750 °C for 6 hours. After cooling, grind it into powder with an agate mortar to obtain the final M'-L.
[0079] The preparation method of 1.25Al-M'-L adsorbent is different from that of M'-L adsorbent in Example 5 in that 0.83 g of silicon source 1.25Al-M' and 2.99 g of LiNO3 are placed in an agate mortar.
[0080] The preparation method of the 1.5Al-M'-L adsorbent is different from that of the M'-L adsorbent in Example 5 in that 0.83 g of the silicon source 1.5Al-M' and 2.99 g of LiNO3 are placed in an agate mortar.
[0081] (3) Testing the adsorption-desorption cycle performance of the adsorbent
[0082] The CO2 adsorption-desorption cycle performance of different samples was tested using a Q50TA Instruments thermogravimetric analyzer (TGA). Samples weighing about 10 mg were taken and adsorbed for 20 min under the conditions of 600 °C and 20% CO2 / N2, and then the temperature was kept constant and desorbed for 20 min in a high-purity N2 atmosphere. This was regarded as one cycle, and so on.
[0083] The recycling performance of the nAl-M'-L adsorbent was determined using the above adsorption-desorption cycle performance testing method. The detection results of the adsorption-desorption cycle performance (Table 5) showed that during the entire adsorption-desorption cycle process, the adsorption capacity of 1.5Al-M'-L after activation reached 16.4 wt%, and the adsorption amount after the adsorption-desorption cycle process reached 15.7 wt%. The adsorption material maintained good cycle stability during the whole process, and the adsorption loss was only 0.7 wt%. This was because by directionally regulating the proportion of the high Curie temperature impurity components in the adsorbent, a supporting effect was provided for the adsorbent, enabling the adsorbent to have anti-sintering ability during the adsorption-desorption cycle process.
[0084] Table 5 Influence of different aluminum contents on the CO2 adsorption-desorption recycling performance of the adsorbent
[0085] Adsorbent type M’-L 1.25Al-M’-L 1.5Al-M’-L Adsorption capacity after activation (wt%) 22.8 15.1 16.4 Adsorption capacity in the 62nd cycle (wt%) 16.2 13.7 15.7 Total adsorption loss in the cycle (wt%) 6.6 1.4 0.7
[0086] (4) Testing the performance of the adsorbent against sulfur oxides, nitrogen oxides, and oxygen
[0087] The performance of 1.5Al-M'-L against sulfur oxides, nitrogen oxides, and oxygen was tested using a Q50TA Instruments thermogravimetric analyzer (TGA). Samples weighing about 10 mg were taken and adsorbed for 30 min under the conditions of 575 °C, 15% CO2 / 1.5 ppm SO2 / 11 ppm NO2 / 6% O2 / N2, and then the temperature was kept constant and desorbed for 30 min in a high-purity N2 atmosphere. This was regarded as one cycle, and so on.
[0088] The performance of the adsorbent against sulfur oxides, nitrogen oxides, and oxygen was determined using the above performance testing method for sulfur oxides, nitrogen oxides, and oxygen. Taking the 1.5Al-M'-L adsorbent as the research object, the detection results ( Figure 4And Table 6) show that at the 3rd cycle, the CO2 adsorption capacity of the 1.5Al-M’-L adsorbent reaches the lowest value of 21.9 wt%, indicating that the presence of SO2, NO2, and O2 may have had a certain impact on the adsorbent performance in the early stage. However, as the number of cycles increases, the adsorbent gradually activates, and the adsorption capacity rebounds to 22.9 wt% at the 13th cycle. After that, the adsorption performance remains stable, still maintaining at 22.9 wt% at the 31st cycle, without obvious regeneration loss. This result shows that although SO2, NO2, and O2 may affect the early adsorption performance of the adsorbent, after a certain cycle activation, 1.5Al-M’-L still exhibits excellent anti-sintering ability and good cycle stability, can maintain stable adsorption performance in an atmosphere where SO2, NO2, and O2 coexist, without obvious performance decay, indicating that the application prospect of this material in the actual flue gas environment is relatively broad.
[0089] Table 6 Adsorption-desorption cycle performance test of 1.5Al-M’-L under flue gas conditions
[0090] Adsorbent 1.5Al-M’-L Adsorption capacity after activation (wt%) 22.9 Adsorption capacity in the 31st cycle (wt%) 22.9 Total adsorption loss in the cycle (wt%) 0
[0091] Comparative Example 1. SiO2-Li4SiO4 adsorbent prepared from traditional commercial SiO2 and lithium-containing compounds
[0092] (1) Preparation method of SiO2-Li4SiO4 adsorbent prepared from commercial SiO2 and lithium-containing compounds
[0093] Place 0.65 g of commercial SiO2 and 2.99 g of LiNO3 in an agate mortar, ensure that the Li / Si molar ratio in the mixture is 4, use ethanol as the grinding medium, fully mix the mixture in the agate mortar, and dry the obtained mixture at 60 °C for 12 hours. Then transfer the obtained mixture to an alumina ceramic crucible and heat it at 750 °C for 6 hours. After cooling, grind it into powder with an agate mortar to obtain the final SiO2-Li4SiO4.
[0094] (2) CO2 adsorption performance test method of the adsorbent
[0095] The adsorption performance of the adsorbents prepared from different silicon sources was determined using the CO2 adsorption capacity test method in Example 1. The test results of the adsorption performance ( Figure 5As shown in Table 7, at low CO2 concentration, the adsorption performance of SiO2-Li4SiO4 is poor, and the adsorption capacity is only 16.2 wt%. Compared with SiO2-Li4SiO4, perlite-Li4SiO4 shows significant adsorption performance advantages at low CO2 concentration, and its adsorption capacity can reach 25.1 wt%. This excellent performance is attributed to the presence of co-adsorbing impurity components in perlite-Li4SiO4, with a silicon-sodium molar ratio of 10.3, which is within the optimal range of sodium content in the adsorbent, thus effectively enhancing the adsorption capacity of the adsorbent at low CO2 concentration.
[0096] Table 7 Effects of different silicon sources on the CO2 adsorption performance of the prepared adsorbents (CO2 concentration: 20%, adsorption time: 2 h)
[0097] Silicon source <![CDATA[Commercial SiO2]]> Perlite Adsorption capacity (wt%) 16.2 25.1
[0098] (3) CO2 adsorption-desorption cycle performance test of the adsorbent
[0099] The adsorption performance of the adsorbents prepared from different silicon sources was measured using the adsorption-desorption cycle performance test method in Example 4. The test results of the adsorption performance ( Figure 6 and Table 8) show that during the entire adsorption-desorption cycle, the adsorption capacity of the SiO2-Li4SiO4 adsorbent decreased by 12 wt%, and at the end of this adsorption-desorption cycle, its adsorption performance showed a continuous downward trend. After 100 adsorption-desorption cycle regenerations of perlite-Li4SiO4, the adsorption capacity of the material only decreased by 1.7 wt%. This indicates that perlite-Li4SiO4 has good cycle stability, which is due to the presence of high-Tammann temperature impurity components in the adsorbent, which can effectively alleviate the sintering of the adsorbent during the adsorption-desorption cycle.
[0100] Table 8 Effects of different silicon sources on the CO2 adsorption-desorption cycle performance of the prepared adsorbents
[0101] Silicon source <![CDATA[Commercial SiO2]]> Perlite Adsorption capacity after activation (wt%) 19.8 24.9 Adsorption capacity in the 100th cycle (wt%) 7.8 23.2 Total adsorption loss in the cycle (wt%) 12 1.7
[0102] Based on the above results, it is obtained that:
[0103] The present invention successfully prepares a material with excellent adsorption performance under low-concentration CO2 conditions and resistance to sulfur oxides, nitrogen oxides, and oxygen by using natural silicon-containing ores or other silicon sources with impurity components. Taking the perlite-Li4SiO4 adsorbent as an example, when the CO2 concentration decreases from 100% to 20%, the adsorption capacity of this material only decreases from 27.3 wt% to 25.1 wt%, showing a high adsorption capacity for low-concentration CO2. In addition, after 100 adsorption-desorption cycles, the adsorption loss of this material is only 1.7 wt%, demonstrating excellent cycle stability. Under flue gas conditions, taking the 1.5Al-M'-L adsorbent as an example, after a certain cycle activation, this material still exhibits excellent anti-sintering ability and good cycle stability, and can maintain stable adsorption performance in an atmosphere coexisting with SO2, NO2, and O2 without obvious performance degradation. The adsorption material prepared by the present invention has important application potential in the field of CO2 capture and storage, especially suitable for long-term stable operation under low-concentration CO2 environments and flue gas conditions.
Claims
1. An adsorbent material resistant to sulfur oxides, nitrogen oxides and oxygen for high-temperature flue gas CO2 capture, which is prepared by using a silicon source such as a silicon-containing precursor, natural silicon-containing ore or other silicon-containing waste containing high-temperature Tamman temperature impurity components (such as Fe, Al, Mg, etc.) and co-adsorption impurity components (such as Na, K, etc.), and reacting with a lithium-containing compound by a solid-phase method; it includes a main adsorbent material Li4SiO4 support component and a co-adsorption component.
2. The high-temperature CO2 capture material according to claim 1, wherein the support component and the co-adsorption component are high-temperature Tamman temperature impurity components and alkali metal or alkaline earth metal impurity components present in the silicon source, the lithium-silicon molar ratio (Li / Si) is 3:1 to 10:1, preferably 4:1, the CO2 adsorption temperature is 400 to 700 °C, preferably 500 to 650 °C, more preferably 600 °C.
3. The silicon source according to claim 1, the adsorption material prepared with the molar ratio of silicon to high-temperature Tamman temperature impurity components (Si / X) in the range of 3.76 to 5.68 has the best effect, X is the high-temperature Tamman temperature impurity element, and the adsorption material prepared under the condition that the molar ratio of silicon to co-adsorption impurity components (Si / Y) is 20.6 or lower has the best effect, Y is the alkali metal or alkaline earth metal impurity element.
4. The method for preparing a silicon-containing precursor according to claim 1, comprising the following steps: (1) Add a structure-directing agent, a pH regulator and deionized water to a beaker and mix at room temperature; (2) Then add the silicon source to the mixed solution and continue stirring; (3) Continue to add inorganic salts of metal elements with high-temperature Tamman temperature characteristics (such as FeCl3, Fe(NO3)3, Fe2(SO4)3, AlCl3, Al2(SO4)3, Al(NO3)3, Mg(NO3)3, etc.) and alkali metal or alkaline earth metal impurity components (such as Na2CO3, K2CO3, etc.) to the mixed solution in proportion, and form a gel-like mixture through mixing and stirring; (4) Subsequently, carry out a hydrothermal reaction on the obtained gel-like mixture; (5) Finally, filter and wash with deionized water until the sample is neutral, and calcine after drying to obtain the silicon-containing precursor containing high-temperature Tamman temperature impurity components (such as Fe, Al, Mg, etc.) and co-adsorption impurity components (such as Na, K, etc.).
5. The preparation method according to claim 4, wherein the structure-directing agent in step (1) is tetramethylammonium, tetraethylammonium, tetrapropylammonium, cetyltrimethylammonium bromide, block copolymer, fluoride, etc., and the pH regulator is ammonia water, NaOH, KOH, organic base (such as TMAOH, TEAOH), hydrochloric acid, sulfuric acid, acetic acid, ammonia-ammonium chloride buffer solution, phosphate buffer solution, etc., and the silicon source added to the mixed solution in step (2) is sodium silicate, silica sol, silica gel, tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate (TMOS), etc.
6. The preparation method according to claim 4, wherein the hydrothermal temperature in step (4) is 80 to 130 °C, the hydrothermal time is 12 to 24 hours, the calcination temperature in step (5) is 450 to 600 °C, and the calcination time is 4 to 6 hours.
7. The preparation method of the high-temperature CO2 capture material according to claim 1 comprises the following steps: (1) Using the above-mentioned silicon-containing precursor or qualified natural silicon-containing ore and silicon-containing waste as the silicon source, mechanically mix it with the lithium-containing compound and the grinding aid; (2) After drying the mixture, calcine it at a high temperature to obtain the high-temperature CO2 capture material.
8. The preparation method according to claim 7, wherein the mass percentage of SiO2 in the natural silicon-containing ore and the silicon-containing waste described in step (1) is between 32 and 90 wt%, such as perlite, diatomite, wollastonite, blast furnace slag, vermiculite or fly ash, etc.
9. The preparation method according to claim 7, wherein the lithium-containing compound described in step (1) is lithium nitrate, lithium carbonate, lithium hydroxide or lithium oxide, etc.
10. The preparation method according to claim 7, wherein the grinding aid described in step (1) is deionized water, ethanol, methanol or acetone, etc., and the calcination temperature in step (2) is 600-800 °C, preferably 750 °C.